(untitled) (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
The purpose of the research was to evaluate the teratogenic effect caused by the provision of Arabica coffee solution with variations of 0.36 ml, 0.72 ml and 1.08 ml with positive control of caffeine at a dose of 300 mg / kg bw to rats during organogenesis. The measurement parameters in this study are the appearance of reproduction, external malformations and scalal malformations. The results in this study found that the administration of Arabica coffee solution with a volume of 1.08 ml and caffeine 300 mg / kg bb caused an abnormality in the reproductive appearance of weight loss and body length, whereas for extrenal malformation and scalal malforation no abnormalities were found in each administration of the solution Arabica coffee and caffeine. Â